Stroke Genetics - Sharma, Pankaj; Meschia, James F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This revised, expanded second edition updates the reader on this fast moving field as well providing an overall understanding of the genetics of complex diseases by using stroke as a paradigm. The reader will gain a comprehensive understanding of cerebrovascular genetics including the epidemiological evidence for the genetic basis of ischemic and hemorrhagic stroke, knowledge of its molecular basis from association, linkage and recent genomewide studies, and also monogenic disorders. Finally, the legal and ethical complexities in dealing with these issues are discussed. Stroke Genetics is a valuable resource for neurologists, stroke physicians, hypertension specialists, internists, clinical pharmacologists and those in training, as well as researchers in the field of disease genetics.
Introduction -- Familial stroke epidemiology -- Association study results -- GWAS -- Aneurysms/carvernous/AVM -- ICH/amyloid/microbleeds -- CADASIL -- Fabry -- MELAS -- Sickle -- Other monogenic -- White matter disease -- Carotid atherosclerosis -- Dissection -- Pharmacogenomics -- Non-Caucasian stroke genetics -- Small vessel disease -- Genetics of neuroimaging in stroke -- Cerebrovenous thrombosis -- Ethics.
Keywords: Medicine; Human genetics; Internal medicine; Neurology; Medicine & Public Health; Neurology; Internal medicine; Human genetics